إعلان "موت الإله " بين قراءتي مارتن بابر و جبرئيل مارسيل - العايب, خميسة (University of Eloued جامعة الوادي, 2018)
الإلحاد عند مارسيل أو كما يسميه بالرفض ليس هو آخر ما تتوصل إليه التجربة، بل إن الشعور بالاكتفاء هو العائق الأكبر أمام مواصلة الطريق نحو الإيمان. وليس وجود الشر في العالم أو المعاناة مبررا لأن العلة هي الهوى الشخصي، إن الرافض على الطريق مثل المؤمن السالك دوما نحو النور بإيمانه ينير الطريق لمن لا يزالون وراءه، لأن طريق الإيمان شاق وملئ بالعثرات وتنمو فيه العقبات مثلما تنمو الأشجار في الغابات العجيبة كما يقول مارسيل وهذا المؤمن هو الذي بنوره يطبق ما يريده مارسيل أن يكون عليه المؤمن كمبدأ وهو " الله يحيا من خلالي لأجلك " كما يدعو إلى ذلك في محاضراته باليابان حينما تناول مسألة العلاقة بين فلسفة الدين والأديان القائمة. The perspective of the existential philosopher Gabriel Marcel on the presence of god is entirely different from that implied by the announcement of the "death of god" Nietzschean. Considered the ultimate or final stage of the investigation of god, Marcel atheism is an evil that has its roots in the concrete and dramatic life of incarnate beings, and it is by refusal or inability to follow the existential path of faith (a path full of obstacles and trials to be overcome by hope, love and fidelity) that the atheist refuses god. Man for Marcel is in the being and at the same time on the way. Communication with the absolute self is inseparable from communication with embodied beings who concretely suffer the dramatic causes of their atheism; the believer is invited to become the light that must guide unbelievers on the path of faith. It is by his refusal of Cartesian or Aristotelian verification that Gabriel Marcel departs not only from Nietzsche, but also from Martin Buber's theory of the eclipse of God .
The Declaration of the "Death of God" between the readings of Martin Baber and Gabriel Marcel
مجلة البحوث والدراسات المجلد 15 العدد02 جامعة الوادي
Keywords: موت الإله ; كسوف الإله ; حضور الإله ; الإلحاد ; الرفض ; الإيمان; Death of God, Eclipse of God, The presence of God, atheism, Faith.